History and memory of the recent past in school: a look at the official proposal (Quinto Sol, 2012)
This paper analyzes the official proposal for recent history teaching. For such purpose, we draw on national education laws (1993 and 2006), the curricula approved from 1995 to present for the secondary level (at the national level and at the Province of Buenos Aires) and regulations of the commemorations –especially March 24th and September 16th–. This analysis will be made in relation to the representations of memory and the progress of historiography about recent past, to consider up to what extent school contents have witnessed an impact due to changes in thesenarratives.
Keywords: history; memory; education laws; curriculum; anniversaries